(untitled) (Journal of Statistical Research, 2025)
In this paper, we introduce a new class of generalized Aradhana distribution with suitable R code termed as area biased generalized Aradhana distribution. The proposed new distribution is a special case of broader weighted distribution family. Its several structural properties have been explored thoroughly and furthermore its parameters have also been estimated based on maximum likelihood estimation. To assess its supremacy, a real life- time data set has been fitted in proposed new distribution to determine its flexibility and superiority in comparison to existing classical distribution. Journal of Statistical Research 2024, Vol. 58, No. 2, pp.353-368